2015
DOI: 10.1080/13621025.2015.1049979
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing lived religious citizenship: a case-study of Christian and Muslim women in Norway and the United Kingdom

Abstract: AcknowledgmentsThe author wishes to thank Esmeranda Manful (UK) and Beatrice Halsaa and Hanna Helseth (Norway) who, as part of the Work Package 4, Strand 2 team of the FEMCIT project, conducted the interviews with religious women. She also wishes to thank the editors of the journal and the anonymous reviewers for their constructive and very useful comments and suggestions. Preliminary project findings were reported in a working paper submitted to the European Union (see Nyhagen Predelli et al. 2010). FundingTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 40 publications
3
25
0
1
Order By: Relevance
“…In this regard, rights-based approaches to religious citizenship (e.g. Hudson 2003) are too narrow (Nyhagen 2015): while they address issues such as freedom of belief and the right to collective worship, they do not consider the importance of belonging, participation, and care. The demonstrated link between citizenship and religion also lends support to the view that religiously informed political convictions are legitimate in democratic deliberation (Habermas 2006).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, rights-based approaches to religious citizenship (e.g. Hudson 2003) are too narrow (Nyhagen 2015): while they address issues such as freedom of belief and the right to collective worship, they do not consider the importance of belonging, participation, and care. The demonstrated link between citizenship and religion also lends support to the view that religiously informed political convictions are legitimate in democratic deliberation (Habermas 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Recent scholarship has also proposed the notion of 'religious citizenship' as useful to debates about the rights of religious citizens and groups (Hudson 2003;Permoser and Rosenberger 2009). Rights-based approaches have, however, been critiqued for paying insufficient attention to inequalities pertaining to gender and to inequalities between majority and minority religions, and for overlooking lived citizenship practice (Nyhagen 2015). In a comparative study of Christian and Muslim women in Norway, Spain and the UK, Nyhagen and Halsaa (2016) found that a majority of the participants saw their faith as strongly linked to their lived citizenship, with their religion providing guidance on how to be a good citizen.…”
Section: Citizenship Gender and Religionmentioning
confidence: 99%
See 1 more Smart Citation
“…To me, issue publics, as based on topological connectives, seem like potential contexts of youth inclusion. If encouraged by public administrative means, they could offer young people what Cornwall and Coelho () call “new democratic arenas” and potential contexts for practicing “lived citizenship,” to use Lister's term (see also Nyhagen ; Wood ). By tracing the issues that appear as particularly important to young people, participatory efforts could aim at supporting youthful agencies in the matters that concern them experientially and thus succeed to “blur the mundane‐political distinction” (Shklovski and Valtysson , 431), thus building connections between the topological worlds of youth and the topographical worlds of public administration.…”
Section: Topological Connectives As Grounds For Issue Publicsmentioning
confidence: 99%
“…In her study of Christian and Muslim women in Norway and the UK, Nyhagen (2015) points out that for women, religious inclusion -she uses the term 'lived religious citizenship' -is about more than individual or group rights. Religious women value belonging, identity and participation.…”
Section: The Case For Religious Inclusionmentioning
confidence: 99%